A new species of Pirhosigma Giordani Soika, 1978 (Hymenoptera, Vespidae: Eumeninae), with additional notes and a key to the species in the genus - Ferreira, Wellington D.; Oliveira, Letícia A. De; Inez, Tiago G.; Hermes, Marcel G. (Zootaxa, 2017)
A new Neotropical species of Pirhosigma Giordani Soika, 1978 is described, Pirhosigma transfluvium Ferreira & Oliveira. The male of Pirhosigma limpidum Giordani Soika, 1978 is reported for the first time. An illustrated identification key is presented for all currently recognized species of Pirhosigma.